2014
DOI: 10.1242/jcs.138495
|View full text |Cite
|
Sign up to set email alerts
|

Sept7bis essential for pronephric function and development of left-right asymmetry in zebrafish embryogenesis

Abstract: The conserved septin family of filamentous small GTPases plays important roles in mitosis, cell migration and cell morphogenesis by forming scaffolds and diffusion barriers. Recent studies in cultured cells in vitro indicate that a septin complex of septin 2, 7 and 9 is required for ciliogenesis and cilia function, but septin function in ciliogenesis in vertebrate organs in vivo is not understood. We show that sept7b is expressed in ciliated cells in different tissues during early zebrafish development. Knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…Freshly dissected skeletal muscle, kidney, and liver tissues were snap frozen in liquid nitrogen, embedded in Tissue-Tek Optimal Cutting Temperature (OCT) compound (Sakura Finetek, Alphen aan den Rijn, The Netherlands), or fixed in 10% formalin, followed by embedding in paraffin. Quantitative RT-PCR was performed as in Dash et al (23). The primers used to amplify phosphoenolpyruvate carboxykinase 1 ( PCK1 ) were the following: forward 5′-CCAAGAGCAGAGAGACACAG-3′ and reverse 5′-CAATACCAATCTTGGCCAGC-3′ and glucose-6-phosphatase ( G6Pase ) forward 5′-CATCAATCTCCTCTGGGTGG-3′ and reverse 5′-TGCTGTAGTAGTCGGTGTCC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Freshly dissected skeletal muscle, kidney, and liver tissues were snap frozen in liquid nitrogen, embedded in Tissue-Tek Optimal Cutting Temperature (OCT) compound (Sakura Finetek, Alphen aan den Rijn, The Netherlands), or fixed in 10% formalin, followed by embedding in paraffin. Quantitative RT-PCR was performed as in Dash et al (23). The primers used to amplify phosphoenolpyruvate carboxykinase 1 ( PCK1 ) were the following: forward 5′-CCAAGAGCAGAGAGACACAG-3′ and reverse 5′-CAATACCAATCTTGGCCAGC-3′ and glucose-6-phosphatase ( G6Pase ) forward 5′-CATCAATCTCCTCTGGGTGG-3′ and reverse 5′-TGCTGTAGTAGTCGGTGTCC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Septins play important roles in diverse cellular processes including cytokinesis (Hartwell, 1971; Kinoshita et al, 1997), cell migration (Dolat et al, 2014; Tooley et al, 2009), neuronal morphogenesis (Tada et al, 2007; Xie et al, 2007), and ciliogenesis (Dash et al, 2014; Hu et al, 2010; Kim et al, 2010; Zhai et al, 2014). Dysregulation of such functions has been implicated in cancer, neuropathy, and infertility (Dolat et al, 2014; Hall & Russell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, several zebrafish studies have indicated the importance of septins for the proper formation and function of cilia, where loss-of-function studies have generated several phenotypes that resemble human ciliopathies (Dash et al, 2014). Hence, an understanding of the role of septins in ciliogenesis at a cellular level is critical to our understanding of ciliopathies.…”
Section: Flagella and Ciliamentioning
confidence: 99%
“…However, septins have more consistently been localized along the axoneme of cilia in many cell types and animal models (Ghossoub et al, 2013; Dash et al, 2014; Fliegauf et al, 2014; Zhai et al, 2014). For example, using various human cells lines such as RPE1 (human retinal pigment epithelial cell line) and hFE (human inner foreskin), Benmerah and colleagues found SEPT2, SEPT7 and SEPT9 to be co-localized along the axoneme in primary cilia and to regulate ciliary length, yet no rings were reported.…”
Section: Localization Of Septins In Ciliamentioning
confidence: 99%
See 1 more Smart Citation